WHAT IT TAKES TO BECOME A SELF-ENTERPRISING HOUSEHOLD IN THE RHODOPE MOUNTAIN, BULGARIA (ЕтноАнтропоЗум, 2019)
Part of the transformations in rural Bulgaria after the fall of socialism in 1989 can be described as the implementation of neoliberal policies, shaped by general trends such as shrinking welfare state, the introduction of markets in public and private spheres and the view that self-enterprising individuals are best equipped to live successful lives in such environment. The latter characteristic can be summarized as the crafting of neoliberal personhood. However, studies from postsocialist settings show that such personhood is always rooted in history and social relationships.This article takes this analysis further by training a spotlight on a form of domestication of Bulgaria’s neoliberalization, whereby the household, the home and the family’s energy became, to certain extent, market assets. It draws on ethnographic fieldwork conducted since 2009 in the southern part of the central Rhodope region. It traces the trajectory of a family who tried to establish a family hotel by extending their house, offering in priority their home-grown food to tourists and harnessing the energies of the household members to this end. Their attempt to receive money support from a programme of the European Union failed. As a result, they found themselves heavily indebted and obliged to work as migrants in the United Kingdom. This case study illustrates how the idea of the marketable self and home have met certain local conditions, thus giving birth to a locally cherished ideal of the commercial home and how difficult is to make this ideal come true.